Peculiarities of reference-retrieval aids of research institutions libraries of SB RAS - A. A. Stukalova (Библиосфера, 2015)
Reference-retrieval aids development prospects in SB RAS research institutes are considered. It is noted that the majority of electronic catalogs present only a part of information on editions, which are available in a library. Besides, some libraries provide information on their collections only in card catalogs. A special attention is paid to such activities as card catalogs retrospective conversion. The author indicates reasons for which libraries do not have the ability to replenish their electronic catalogs with retrospective information.